Relationship between Multivalent Cation Charge Carriers and Organic Solvents on Nanoporous Carbons in 4 V‐Window Magnesium Ion Supercapacitors (Adv. Energy Mater. 30/2021). Issue 30 (12th August 2021) - Moon, Seongbak; Lee, Sang Moon; Lim, Hyung‐Kyu; Jin, Hyoung‐Joon; Yun, Young Soo
Abstract : Supercapacitors In article number 2101054, Hyung‐Kyu Lim, Hyoung‐Joon Jin, Young Soo Yun and co‐workers conduct an extensive study on the capacitive Mg‐ion storage behavior of nanoporous carbons in different organic solvents. High‐performance 4 V window Mg‐ion supercapacitors based on ultramesoporous carbons, which can deliver specific energy densities of 106 Wh kg −1 and power densities of 11 870 W kg −1 over 10 000 cycles are achieved.